(untitled) (Altre Modernità, 2012)
Angela Carter’s Japanese experience (1970-1971) profoundly affected the writer, influencing all her following works. The collections Nothing Sacred (1982) and Fireworks: Nine Profane Pieces (1974), gathering respectively journalistic writings and short stories, show how the Japanese years prompted to strengthen her criticism towards the Western patriarchal tradition and to codify a new paradigm for the representation and enactment of performative female identity(-ies). As it has been argued, Carter’s perspective is that of a Western tourist, looking down on Japanese culture and society with an imperial gaze. However, this very point of view proves to be both problematic and productive, for her being a Western foreigner (the imperial Eye), combines with her being a woman, a subject who speaks from an unprivileged position, the subordinated Other in her homeland. Moreover, as Carter declared, she did not know nor was able to learn the Japanese language, thus being forced –and willing- to observe reality with sharpened senses in order to name everything anew, starting from her self-perception of what it means to be a woman and to act as one. Thus, the author fills in Japanese empty signs with brand new meanings and begins to build up a new system of signification from the ambivalent perspective of a foreign woman, whose otherwise underprivileged position is empowered by the fact of being British. Her impressions of the Japanese world and her reasonings about gendered identities are then conveyed though the powerful, omnipresent image of the mirror. In Carter’s wor(-ds)k mirrors and reflections are at the same time both the means which make disruptive and original models and performances possible and effective ways to represent them, since it is through the reflection/projection of Japanese culture into the Western one and through the mirroring of the female subject in the other’s eyes, that female subjectivity is endowed with a new –subversive- potential.